Influences of elastic foundations on the nonlinear free vibration of composite shells containing carbon nanotubes within shear deformation theory. (15th April 2022) - Avey, M.; Fantuzzi, N.; Sofiyev, A.H.; Kuruoglu, N.
Highlights: Nonlinear (NL) vibration of shells patterned by CNTs on elastic soils within SDT is presented. Basic equations of shells within SDT are established considering the geometric nonlinearity. Frequencies of NL and L vibrations of nanocomposite shells on soils within SDT are obtained. Influences of some parameters on the frequency-amplitude dependence are carried out. Abstract: In this work, the solution of nonlinear free vibration problem of composite shells structures containing carbon nanotubes (CNTs) resting on elastic soils within shear deformation theory (ST) is presented. After modeling the mechanical properties of nanocomposite shell structures containing CNTs and elastic soils, the basic relations, and governing equations of double curved shell structures within the ST are established considering the geometric nonlinearity. The frequencies of nonlinear and linear free vibrations and their ratios for inhomogeneous nanocomposite structures on the soils within the ST are obtained using perturbation method for the first time. After checking the methodology of the research, the effects of soils, nonlinearity, shear strains and patterns of CNT on the frequency-amplitude dependence of nanocomposite shell structures for various geometric parameters are carried out.